Diseño urbano parque lineal zona ambiental pulmón verde, promoveedor de concientización educación e interacción ambiental en Carvajal, Bogotá D.C. (2022)
Today a topic that is talked about all over the planet is air pollution, this problem generates effects on human health. The potential to avoid this affectation is to create spaces for urban-landscape renewal in the Bogotá sector in the Carvajal upz by the area of ​​the old southern railway, therefore, this strategy of generating landscaped green areas with forestry is implemented to help improve the quality of the air derived from the combustion of cars and industries.The park that will be strategically designed with the theory of bioclimatic design and the equipment that will accompany the urban proposal is a botanical garden that is focused on the conservation of the park itself and will also have a repetition model of recreation, bone and vegetation areas, the establishment through forestry depending on the species of trees that help reduce the pollution of particles and gases.